2005
DOI: 10.1016/j.femsyr.2005.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol oxidase: A complex peroxisomal, oligomeric flavoprotein

Abstract: Alcohol oxidase (AO) is the key enzyme of methanol metabolism in methylotrophic yeast species. It catalyses the first step of methanol catabolism, namely its oxidation to formaldehyde with concomitant production of hydrogen peroxide. In its mature active form, AO is a molecule of high molecular mass (600 kDa) that consists of eight identical subunits, each of which carry one non-covalently bound flavin adenine nucleotide (FAD) molecule as the prosthetic group. In vivo, the protein is compartmentalized into spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 97 publications
(105 reference statements)
3
72
0
Order By: Relevance
“…Methanol oxidase.-MOX is mostly known as a peroxysomal enzyme in methylotrophic ascomycetous yeasts, such as Pichia pastoris or C. boidinii (Ozimek et al 2005). The first basidiomycete MOX was purified and characterized from P. chrysosporium (Nishida and Eriksson 1987) and it is also known from Phlebiopsis gigantea (Danneel et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Methanol oxidase.-MOX is mostly known as a peroxysomal enzyme in methylotrophic ascomycetous yeasts, such as Pichia pastoris or C. boidinii (Ozimek et al 2005). The first basidiomycete MOX was purified and characterized from P. chrysosporium (Nishida and Eriksson 1987) and it is also known from Phlebiopsis gigantea (Danneel et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Riboswitches are the nontranslated mRNAs that bind effectors (low-molecular-weight metabolites) using selective binding domains (otherwise called ligand-binding pockets or aptamers) without a requirement for any proteins. Regulation of gene 338 ABBAS AND SIBIRNY MICROBIOL. MOL.…”
Section: Transcriptional Regulation In Bacteria Using the Riboswitch mentioning
confidence: 99%
“…The characteristics of those AODs and the regulation of the gene encoding AODs have been studied in detail (Couderc and Baratti, 1980;Kato et al, 1976;Ozimek et al, 2005;Tani et al, 1972Tani et al, , 1985. In the production of AODs by filamentous fungi, Ko et al have recently reported that Thermoascus aurantiacus NBRC 31963 inductively produced two AODs by incubation with the pectin medium, and characteristics of both enzymes have been revealed by his group (Ko et al, 2005).…”
Section: Introductionmentioning
confidence: 99%